Dvylikos Olimpo dievų vaizdavimas Enijaus Analuose - Veteikis, Tomas (Literatūra, 2008)
Annales of Ennius, partly aimed at survey of Roman history year by year, partly at memorizing Roman heroes and equating them to gods, though had a few antecedant models in Hellenistic epic, remains unrivalled in respect of vastitude and bravery of the innovatory devise. The poem, praising deeds of Roman god-like ancestors, kings, consuls and tribunes, had certain political aspirations tending to melt the scepticism towards Greek culture and its reception among conservative members of aristocracy of Ennius’ time. On the other hand, being performed in traditional Roman convivial setting, Annales were in accord with Roman piety and reverent attitude towards gods, whence poet’s aim at his own otherness and impartiality might be discerned. Annales of Ennius not only reminds its readers of Roman strategy of gaining over Carthaginian or Greek deities during Roman expansion outside Appenines, but also claims their common identity with Roman gods, whence the idea of Greek and Roman cultural affinity and common genealogy comes. This idea most probably originates from the deep consideration of homeric and hellenistic epic and their exegetical traditions combined with other philosophical views (even contrasting ones) attainable in III B. C. Italy. However, the state of extant text of Annales, consisting of over 600 fragmentary verses (plus around 100 more or less identified testimonia together with recently deciphered fragments from Herculanean papyrus), doesn’t provide us with certain argument what attitude in Ennius’ notion prevailed, unless we investigate one by one all the mentions of gods in this poem. The complex task is treated in this article in a selective manner: the main attention is paid only to the limited part of over 40 deities present in Annales, namely, to the Greco-Roman dodekatheon or di consentes, most clearly attested in Ann. 240–241 Sk. The method of investigation rests on the description of each deity separately, both trying to establish the most characteristical features of each in Ennian depiction and compare with the evidence of his / her contemporary cult and degree of syncretization. In the course of analysis, a somewhat parallel attempt is also made to verify Cicero’s message concerning Ennius’ belief in gods in general (Div. 1, 58). The analysis shows quite divergent result resting upon incomplete status of our sources: some gods are depicted as participants of human actions, some remain mere vague representatives of natural phenomena. The bulk of conclusions deals with national dependance, hierarchy and stylistic variation of Ennius’ dodekatheon. Material of this paper clearly indicates the national priority in Annales: the most honoured both statistically and virtually are the four ancestral Roman gods (di genitales) – Juppiter, Juno, Venus and Mars. Each of them also appears in certain non-Roman context (Trojan, Greek, Carthaginian or Sabinian), where their Roman priority is not emphasized, unless their Latin name is taken into account. The latter fact combined with Ennian technics of Homer’s imitation and hellenistic erudition enables him to rewrite ancient history from the Roman point. This actually happens on the theological level when Roman state gods become continuators of variously reinterpreted homeric greco-trojan gods. Annals of Ennius thus attest the absorbtion of Greek Olympic pantheon into Roman state pantheon. Depiction of gods in the poem also has certain “expurgatory” mark, since very few traces of obscenity in gods’ portrayal are present (with exception of Mars, called homo pulcer with possibly euhemeric hint). On the other hand, the sublimity of Ennian gods is moderate: there are several indications of their humanly sensitive and not indifferent stance in their contacts with people (esp. Juno, Juppiter and Venus). A considerable group of Olympian gods in the current fragmentary shape of Annals remains not clearly presented: some produce no material for deeper analysis (e. g. Diana and Ceres), some appear only in the metonymic use (Neptune, Volcanus), others could be characterized on the ground of mere indirect reference to their ritual elements, mythological or allegorical identity (Vesta, Minerva, Mercurius). Permanent attention to universal aspects, esp. to the mysthic and prophetic ones (Minerva, Apollo, Muses), and avoidance of “undignified” features show perhaps definite poet’s attitude and support modern view of Ennius’ both honorable and impartial position towards Roman “political Olympus”.